Los métodos y técnicas de enseñanza-aprendizaje utilizados por los docentes de física en los bloques curriculares: movimiento de los cuerpos en una y dos dimensiones y su incidencia en el desarrollo de destrezas con criterio de desempeño de los estudiantes del primer año de bachillerato general unificado del colegio Dr. Miguel Riofrío unidad educativa intercultural bilingüe Mushuk Rimak de la parroquia San Lucas, cantón y provincia de Loja; período 2012-2013. Lineamientos alternativos - Lozano Guaillas, Rosa Etelvina (2013)
The research work entitled "Methods and techniques of teaching and learning used by physics teachers in curricular blocks: motion of bodies in one and two dimensions and its impact on skills development with performance criterion Prime students General High School Year Unified school "Dr. Miguel Riofrio "Bilingual Intercultural Education Unit of the parish Mushuk Rimak San Lucas, county and province of Loja 2012-2013 period", as a need to contribute to the improvement of education quality and innovation of teaching methods and techniques - learning to develop skills with performance criteria students. The specific objectives that guided this research are: Determine how the knowledge they have physics teachers on methods and techniques of teaching and learning in curricular areas: Movement of bodies in one and two dimensions, influence the development of skills performance criteria of students surveyed; determine the mode of application of methods and techniques of teaching and learning in curricular areas: movement of bodies in one and two dimensions and its impact on skills development performance criteria in the students, raise methodological alternative guidelines to improve the level of skills development with performance criterion under study students. Finally, analyzing the results, it is determined that all teachers use the deductive method for teaching and learning of the blocks in the study, half of the teachers work with active learning techniques, dictation, and experience the dialogue, likewise, students respond to the teacher asks questions and memorize forces and does not allow asking. These methods and techniques of teaching and learning are not suitable for teaching the curriculum blocks and there is no evidence in the educational activity, this shows a lack of experience and didactic training of teachers in charge of the course, teachers should implement several methods to develop skills with performance criteria students. Moreover, in the educational institution exists partly concrete material, thus does not contribute significantly to the training of students, limiting the development of skills with performance criteria objectively students.